Developing Hot Mathematics Task with Indonesian Heritage as Context to Assess Mathematical Literacy of Students in Primary School - Oktiningrum, Wuli; Wardhani, Dyah Ayu Pramoda (Universitas Malikussaleh, 2020)
The goal of this research produces a set of HOT mathematics tasks with Indonesian heritage as a context that is valid and practical to assess the mathematical literacy of students in primary school. The participants of the study were 120 students in primary school. The data was collected through documentation, questionnaire, test result, and interviews. This is design research using a type of development research with formative evaluation. The mathematics task not only reviewed by 7 experts, who assess the context, content, and language of prototype but also beyond empirical evaluation of validation and reliability testing. The field test result showed that the HOT mathematics task has a potential effect on the mathematical literacy of primary school students.